The Influence of Work Life Balance, Workload, and Work Environment on Organizational Commitment to Employment BPJS in Mojokerto - Latifah Rukmiati Ifnu Jafar; Budi Prabowo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of work-life balance, workload, and work environment on organizational commitment at BPJS Ketenagakerjaan in Mojokerto. This type of research is associative quantitative with a population of all employees of BPJS Ketenagakerjaan Mojokerto, totaling 40 people. Data collection techniques using questionnaires and analysis techniques using multiple linear regression using SPSS 30 software. The results showed that work-life balance, workload, and work environment simultaneously had a significant effect on organizational commitment. Partially, work-life balance, workload, and work environment each have a significant positive effect on organizational commitment. These findings indicate the importance of managing workload, creating work-life balance, and a supportive work environment in increasing employee commitment to the organization.